Et leilighetsdikt av Johan Herman Wessel - Bliksrud, Liv (Danske Studier, 2011)
The occasional poem by Johan Herman Wessel (1742–1785) which is presented here, has not been known to the public until recently. It was found in the Danish National Archive in Copenhagen (in the archive of Hegermann-Lindecrone) by Jens P. Sørensen. The poem is a letter in verse form addressed to the Norwegian poetess Magdalene Sophie Castberg (1755–1825), written in a mocking, playful manner rich in erotic allusions. Wessel’s play on male and female roles and identities adds spice to the presentation.